Park Street looking towards Beacon Street, ca. 1860-1900 - Unknown (Tufts Archival Research Center, 2005)
Street-level view northwest of Park Street looking towards Beacon Street. The dome and facade of the Massachusetts State House, located on Beacon Street, are visible in the background of the photograph. Awnings and wrought iron railings adorn the facades of buildings lining the northeast side of Park Street. The southwest elevation of the Park Street Church, located on the northwest corner of Park and Tremont Streets, is visible along the right side of the photograph. The Boston Common, visible along the left-side of the photograph, is separated from Park Street by a wrought iron fence. A horse-drawn wagon is visible along the northeast side of Park Street, which is lined with street lights. 7 x 4 1/4, 7 9/16 x 4 3/4 overall Albumen prints